(untitled) (Педагогіка вищої та середньої школи, 2007)
This social-hygienik characteristic of the some negative consequense the imperfection in region the moral and valeological training of schoolboys and young people of Krivoy Rog. Future improvement in the qualities of the educational of work requires the more complete calculation of social-economical and political realias of modern reorganization processes in the Ukraine.